2011
DOI: 10.1007/s00432-011-1030-0
|View full text |Cite
|
Sign up to set email alerts
|

BIRC5 promoter SNPs do not affect nuclear survivin expression and survival of malignant pleural mesothelioma patients

Abstract: Our findings indicate no relationship between BIRC5 genotypes and survivin expression or overall survival in mesothelioma patients. We observed that BIRC5 -241C > T polymorphism had a significant effect on patient age at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…Gordon et al detected 76 % of survivin positive malignant pleural mesotheliomas (Gordon et al, 2007), which is in concordance with the 77 % of survivin positive malignant pleural mesotheliomas detected by (Klabatsa et al, 2005), whereas Kleinberg et al demonstrated survivin expression in 64 % of malignant pleural mesothelioma patients included in their study (Kleinberg et al, 2007). In comparison, in our recently published paper, all (100 %) of the malignant pleural mesothelioma specimens from 101 patients analysed were survivin positive, with a median level of 67 % of survivin positive tumour cell nuclei (Hmeljak et al, 2011 (Hmeljak et al, 2011) *Only patients with malignant pleural mesothelioma are included, although some of the studies comprised malignant peritoneal mesothelioma and reactive pleuritis patients. Table 2.…”
Section: Prognostic Rolesupporting
confidence: 82%
“…Gordon et al detected 76 % of survivin positive malignant pleural mesotheliomas (Gordon et al, 2007), which is in concordance with the 77 % of survivin positive malignant pleural mesotheliomas detected by (Klabatsa et al, 2005), whereas Kleinberg et al demonstrated survivin expression in 64 % of malignant pleural mesothelioma patients included in their study (Kleinberg et al, 2007). In comparison, in our recently published paper, all (100 %) of the malignant pleural mesothelioma specimens from 101 patients analysed were survivin positive, with a median level of 67 % of survivin positive tumour cell nuclei (Hmeljak et al, 2011 (Hmeljak et al, 2011) *Only patients with malignant pleural mesothelioma are included, although some of the studies comprised malignant peritoneal mesothelioma and reactive pleuritis patients. Table 2.…”
Section: Prognostic Rolesupporting
confidence: 82%
“…Several studies have now indicated that higher levels of XIAP may contribute to chemotherapy resistance in mesothelioma cells (32,33). Survivin was also found actively expressed in MPM (32,34) and it has an important role in maintaining apoptosis resistance. It can partially block activation of caspases due to its ability to bind to activated caspases (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…One aspect of cancer is that apoptosis is uninhibited. Survivin, an inhibitor-of-apoptosis protein, is encoded by BIRC5, a gene that is linked to the regulation of apoptosis and cell division (Moore et al, 2014;Hmeljak et al, 2011). Studies have shown that BIRC5 is a biomarker for Oral Squamous Cell Carcinoma as well as breast, liver and prostate cancer.…”
Section: P53_signaling_pathwaymentioning
confidence: 99%